Systematic Literature Review (SLR): Analyzing the Important Role of Population and Human Resource Development - Rahmat Rahmat; Isnaini Harahap; Zuhrinal M. Nawawi; Ade Khadijatul Z Hrp (Institute of Computer Science (IOCS), 2024)
The beginning of the New Order era which then became a national program with the issuance of various strategic policies such as family planning program and establishing an institution that specifically handles population control and family planning and then gained momentum in the 90s which succeeded in reducing the population growth rate to 1.44%. The solutions provided to address population problems and human resource development in Indonesia above include: 1) Increasing the workforce, expanding markets, improving health, increasing productivity of the poor, increasing employment power, reducing non-working days and increasing output. 2) Requires having high competence in terms of planning, implementing plans, organizing, leadership, supervising or controlling development, so that good institutional management is required. 3) Providing management of capital accumulation, exploring natural resources, building social, economic and political organizations for the implementation of economic activities. 4) Improve abilities and skills, human resources through education so that they have high competitive value. 5) Improve communication between implementors, stakeholders, cross-sector partners and the community